Impacts of Capital Structure, Liquidity, and Earnings Quality on Firm Value of Indonesia Non-Cyclicals Industry - Ester Tri Utami; Muhammad Daffa Al Ghazy; Albert Luhut Hamonangan Pasi (Cita konsultindo, 2023)
Firm value plays an important factor to determine company performance. This paper aims to analyse the impacts of capital structure, liquidity, and earnings quality on firm value of Indonesia non-Cyclical Industry. The research is conducted by using purposive sampling analysis from IDX NON-CYCLICAL firms with secondary data collected from Indonesia Stock Exchange. Multiple regression analysis with SPSS shows that capital structure and earnings quality have no significant impact on firms' value, whereas liquidity shows positive and significant influence. Besides extent the prior literatures, this research help investors to understand how non-Cyclical companies performed during 2017- 2021 where firm's financial policies and performance might be affected by Covid-19. Companies' management is also expected to pay more attention to stabilize and maximize the performance factors of firms' value.